The Influence Of Internal And External Factors On Members' Decisions In Taking Murabaha Financing - Denisa Hadiani; Suharti Suharti; Nur’aeda Nur’aeda (LPPM ISNJ Bengkalis, 2023)
Murabaha financing is the most common type at BMT Ash-Shaff Pringgarata because it is prioritized over other financings. Two factors can influence members' decisions in taking Murabaha financing: internal factors, including perception, motivation, and personality, and external factors, including culture and social class. This study aims to show the influence of internal and external factors on members' decisions in taking Murabaha financing at BMT Ash-Shaff Pringgarata. This type of research is associative quantitative. The data source used is primary data using a questionnaire collecting data. The population of this study is members who receive Murabaha financing for the 2017-2021 period, totalling 2351 people. The sample measurement uses the Slovin formula, with a sample of 100 people using the incidental sampling technique. The data analysis technique used multiple linear regression tests using the IBM SPSS program version 25. The results showed that internal and external factors partially or simultaneously influenced members' decisions to take Murabaha financing at BMT Ash-Shaff Pringgarata. This research can complement existing theory and be a reference for BMTs to evaluate the strategies used to attract members to take up financing.